HMM as an inference technique for context awareness - Abdul Matin, Ahmad Faridi; Rahman, M.M. Hafizur (Elsevier Ltd., 2015)
Context awareness is an important element in the pervasive and ubiquitous computing. It involves the ability of the computing system to be aware of the context in which a particular target user is experiencing. This involves the location in which the target is, the activity that the target is doing, the identity of that target and the time in which the activity occur. Once these two elements are known we propose the use of HMM to predict and infer the context of the user.